An Atypical Case of Mild COVID-19 Infection with Severe Guillain-Barré Syndrome as Neurological Manifestation - Behera, Debasis; Behera, Ruchi Rekha; Jagaty, Suman Kumar; Das, Rekha; Venkataram, Rajesh; Subhankar, Saswat; Samal, Vikram (Journal of Health and Allied Sciences NU, 2021)
Introduction More than 80 million people have been infected with coronavirus disease 2019 (COVID-19) infection worldwide till date with more than 17,00000 fatalities. Although COVID-19 commonly affects respiratory system in the form of cough and dyspnea, a neurotropic presentation has been described in one-third of patients.Objective We report an atypical case of COVID-19 with mild symptoms who presented to our hospital with features suggestive of severe Guillain-Barré syndrome (GBS).Discussion The mechanisms by which severe acute respiratory syndrome coronavirus 2 causes neurologic damage are multifactorial, including direct damage to specific receptors, cytokine-mediated injury, secondary hypoxia, and retrograde travel along nerve fibers. The pathogenesis of GBS secondary to COVID-19 is not yet well understood. It is hypothesized that viral illnesses-related GBS could be mediated due to autoantibodies or direct neurotoxic effects of viruses.Conclusion In this ongoing era of pandemic, it is very important for the clinicians to be aware of association of GBS with COVID-19, as early diagnosis and treatment of this complication could have gratifying results. It is also very important to differentiate GBS from critical illness neuropathy and respiratory distress secondary to COVID-19 itself, as treatment to the above conditions is quite different and inability to correctly diagnose could lead to significant increase in morbidity and mortality.
Keywords: COVID-19; GBS; AMSAN; lung collapse; bronchoscopy